Armstrong [videorecording (DVD)] - Ford, Harrison, 1942- (Gravitas Ventures, 2019)
Dramatic, moving and insightful, this documentary tells the definitive life story of Neil Armstrong: from his childhood in rural Ohio, through aerial combat in Korea, to his first steps on the Moon, and the unwanted celebrity status that ensued.